2020
DOI: 10.1002/ejhf.2025
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring in patients with chronic heart failure and moderate depressed symptoms: results of the Telemedical Interventional Monitoring in Heart Failure (TIM‐HF) study

Abstract: Aims Depression is a frequent comorbidity in patients with chronic heart failure (CHF). Telemonitoring has emerged as a novel option in CHF care. However, patients with depression have been excluded in most telemedicine studies. This pre‐specified subgroup analysis of the Telemedical Interventional Monitoring in Heart Failure (TIM‐HF) trial investigates the effect of telemonitoring on depressive symptoms over a period of 12 months. Methods and results The TIM‐HF study randomly assigned 710 patients with CHF to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 27 publications
1
46
0
2
Order By: Relevance
“…[ 2 , 18 , 19 ] TM has also been shown to improve depressive symptoms and quality of life in HF patients with moderate depression. [ 20 ]…”
Section: Telemedicine In Heart Failure: Remote Patient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 , 18 , 19 ] TM has also been shown to improve depressive symptoms and quality of life in HF patients with moderate depression. [ 20 ]…”
Section: Telemedicine In Heart Failure: Remote Patient Managementmentioning
confidence: 99%
“…The need for HF patient empowerment and proximity care, which can be addressed by TM, and will become a relevant tool in promoting a personalised medicine. [ 2 4 , 9 , 19 , 20 , 40 ]…”
Section: The Digital Transformation Of Heart Failure Carementioning
confidence: 99%
“…39 TIM-HF2 (Telemedical Interventional Management in Heart Failure II study) trial showed a positive impact of telemedicine on unplanned CV hospitalization and mortality. [234][235][236] The HOME-HF study was designed to assess the feasibility and efficacy of BNP home measurement in reduction of HF-related events. It was early interrupted because of slow enrolment, low event rate, and the need of standardize BNP spontaneous fluctuation.…”
Section: Telemedicine and Disease Managementmentioning
confidence: 99%
“…Home telemonitoring is a useful tool for the management of HF patients 39 . TIM‐HF2 (Telemedical Interventional Management in Heart Failure II study) trial showed a positive impact of telemedicine on unplanned CV hospitalization and mortality 234–236 . The HOME‐HF study was designed to assess the feasibility and efficacy of BNP home measurement in reduction of HF‐related events.…”
Section: Devicesmentioning
confidence: 99%
“…patient self‐managed testing, wearable devices, technologies integrated into pacemakers and defibrillators) 26 . In a pre‐specified analysis of the TIM‐HF (Telemedical Interventional Monitoring in Heart Failure) trial, telemedicine significantly improved symptoms of depression and quality of life over a period of 12 months 27 …”
Section: Disease Managementmentioning
confidence: 99%